(untitled) (International Journal of Geoscience, Engineering and Technology, 2020)
With the change in the last decades of the Brazilian model of water management by Law 9.433/1997 of the National Water Resources Management Plan, the national system began to qualitatively evaluate, in addition to quantitatively, the issues related to Water Resources. New approaches to environmental, sanitation, and public health demands began to be part of the new model and thus a broad yet timely interface were established in water planning. The present article sought to compare social and public health indicators, such as the main diseases, with indicators of basic sanitation and those related to water quality, at national level and taking into account a historical series of data, as base year 2.000. From the analysis, it was verified that the improvement in the living conditions of the population was directly related to the water quality in the supply and collection of sanitary sewage, and a decrease of indicators when analyzed the historical series.